Urethroplasty for Long Anterior Urethral Strictures: Report of Long-term Results - Moradi, Mahmoudreza; Moradi, Asâ€™ad (Urology Journal, 2009)
Introduction: We reviewed the long-term outcome of substitution urethroplasty with skin flaps for anterior urethral strictures, comparing 1-stage with 2-stage repairs. Materials and Methods: A total of 45 patients with urethral strictures, 2.5 cm or longer, had undergone skin flap urethroplasty. A 1-stage surgical operation had been done in 10 patients (Orandi and bilateral pedicle island of penile skin) and a 2-stage surgical repair had been performed in 35 using the Johanson technique. They were followed up by retrograde urethrography for 1 to 10 years. Results: The mean age of the patients was 46.3 Â± 17.1 years. Etiology of the stricture was instrumentation in 33.3% of the patients, urethritis in 28.9%, trauma in 13.3%, and unknown in 24.5%. At the first postoperative year, the success rate was 75.6%. This rate was 71.4% and 90% for the 1-stage and 2-stage operations, respectively (P = .23). There were 1 (10%) and 10 (28.6%) cases of recurrent structure and 1 (10%) and 3 (8.6%) cases of fistula in the patients with the 1-stage and 2-stage operations within the first year, respectively. During the 5 postoperative years, 70% of the patients with the 1-stage repair, 57.1% with the 2-stage repair, and 60% in total had no complications. Conclusion: Based on the previous studies and our experience, we recommend skin flap urethroplasty. However, some measures such as proper tailoring of the flap and the extension of the incision onto the intact segments should be considered for achieving a better outcome.